Fiscal capacity and public health expenditure in Zimbabwe - Tamisai Chipunza; Senia Nhamo (Taylor and Francis Group, 2023)
Public healthcare financing is important for achieving one of the 2030 Sustainable Development Goals (SDGs), the goal of healthy living and well-being (SDG3). Understanding the impact of fiscal capacity on public healthcare financing helps in assessing the government’s commitment towards attaining SDG3. The study sought to investigate the relationship between fiscal capacity and public health expenditure in Zimbabwe. An Autoregressive Distributed Lag (ARDL) model was estimated using annual time series data for the period 1980–2017. The results of the ARDL model were validated using the Fully Modified Ordinary Least Squares (FMOLS) and Canonical Cointegrating Regression (CCR) methods. The study found that fiscal capacity (measured as the ratio of tax revenue to GDP) impacted positively on public health expenditure. The results suggest that following an improvement in resources, the government prioritised the health sector. The study recommends that the government continues to prioritise health in the national budget to enhance the country’s achievement of SDG3.